KEPUASAN BELAJAR SISWA DALAM PEMBELAJARAN IPAS (KIMIA) BERBASIS SEMINAR KELAS X SMK ABDURRAB PEKANBARU : IMPLEMENTASI KURIKULUM MERDEKA - Yulia Safitri (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2023)
Learning that is commensurate with the teaching method and learning material to be taught can increase student learning motivation. The purpose of this study was to determine the effect of the implementation of Merdeka  curriculum on science (chemistry) learning on the learning satisfaction of students of class X SMK Abdurrab Pekanbaru. This research method is descriptive qualitative. The sample in this study was 132 grade X students of SMK Abdurrab Pekanbaru. The result of this study is that the overall level of satisfaction is very good. This is evidenced by the percentage of satisfied answers of 67.4%, while very satisfied is 18.9%, and only a small percentage of students who answer less satisfied by 13.6%. This shows that the learning method carried out is very well continued. In addition, other aspects can also be developed such as self-confidence, the ability to provide ice breaking, innovative and creative quizzes, very useful to support students' careers in the world..